Age-related Bilateral and Unilateral Lower Extremity Strength Imbalances in Elite Soccer - Çakır, Halil İbrahim; Kayhan, Recep Fatih; Terzi, Esranur (International Journal of Sports Medicine, 2025)
This study investigates bilateral and unilateral strength imbalances in elite young football players across different age categories. A total of 73 licensed male football players in the U15, U16, U17, and U19 age categories participated in the study. Imbalances between the legs were assessed by both jump tests and differences between hamstring and quadriceps strengths. Differences between age groups were statistically evaluated by one-way analysis of variance and linear regression analysis. The results showed that the hop test asymmetry index (AI), Q/Q, and H/H strength ratios decreased from U15 to U17 and increased again at U19 (p=0.037, p=0.025, p=0.002). Regression analysis revealed that age significantly influenced the hop test AI (5%), Q/Q strength ratio (5%), H/H strength ratio (12%), and dominant leg H/Q strength ratio (7%) (p<0.05). Overall, this study shows that muscle strength imbalances in young soccer players differ both bilaterally and unilaterally with age. While bilateral strength differences were relatively balanced in the U15–U17 age groups, a significant asymmetry was observed in the U19 group. In terms of unilateral strength, a certain development was observed in the dominant leg with age, while this development was limited in the nondominant leg.
Keywords: asymmetry index; functional jump test; isometric strength; injury risk